Fragmentation dynamics of CH3Clq+ (q = 2, 3): theory and experiment. Issue 45 (19th October 2022) - Bhatt, Pragya; Maiyelvaganan, K. R.; Prakash, M.; Palaudoux, J.; Safvan, C. P.; Hochlaf, M.
Abstract : We use advanced theoretical treatments and energetic ion collision induced fragmentation to investigate the unimolecular decomposition dynamics of CH3 Cl q + ( q = 2, 3) ions, where both obvious bond breaking and bond rearrangement products are observed. Abstract : A combined theoretical and experimental study of the dissociation of the di- and trication of the CH3 Cl molecule has been performed. Experimentally, these multi-charged ions were produced after interactions of a CH3 Cl effusive jet with a mono-energetic beam of H + or Ar 9+ projectile ions. Theoretically, we mapped the multi-dimensional potential energy surfaces of CH3 Cl 2+, H2 CClH 2+ and CH3 Cl 3+ species in their electronic ground and electronically excited states using post-Hartree–Fock configuration interaction methods. In addition to the obvious bond-breaking ionic fragments ( i.e. H + + CH2 Cl +, H + + CH2 Cl 2+ and CH3 + + Cl + ), the formation of H2 + (+CHCl + or CHCl 2+ ), H3 + (+CCl + ) and HCl + (+CH2 + ) was observed upon bond rearrangement after ion impact of CH3 Cl. The interaction strength of the incident projectiles is found to affect the relative yields on the observed dissociation channels, however, it has no effect on the kinetic energy releases of the fragmentation pathways. For the observed dissociation channels, plausible formation mechanisms were proposed. These reaction pathways take place on the ground and/or electronic excited potential energy surfaces of the doubly and triply charged CH3 Cl ions, where spin–orbit and vibronic couplings are in action. Moreover, this work suggests that the mechanisms undertaken may depend on the multiply charged ion preparation by valence or inner-shell single photon photoionization, fast ion beam impact or ultrafast intense laser ionization.